Perlindungan Hukum terhadap Konsumen dalam Transaksi E‑Commerce di Indonesia - Muhammad Fahrurozi; Romi Faslah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Legal protection for consumers in e‑commerce transactions is crucial to maintaining trust in the digital economy. This study analyzes the legal frameworks governing online consumer protection in Indonesia, focusing on Law No. 8/1999 and PP No. 80/2019. Using a normative‑juridical method, it examines legal provisions and their implementation gaps. The findings show regulatory existence but highlight enforcement weaknesses, limited consumer awareness, and challenges in cross‑border protections. Recommendations include strengthening enforcement, improving digital literacy, and establishing robust dispute resolution mechanisms.